Learning Direct and Inverse Proportion Using Pen and Money for Slow-Leaners - Kartika Dyah Wardani; Rully Charitas Indra Prahmana (Indonesian Research Journal in Education |IRJE|, 2021)
Students who have slow mathematical cognitive abilities or slow learners usually have difficulties understanding an abstract mathematical concept. One alternative learning that can improve the mathematical understanding of slow learners is the Indonesian Realistic Mathematics Education (IRME) approach. Therefore, this research aimed to determine the learning process and the role of IRME to improve the cognitive mathematics ability of slow learners about the concept of direct and inverse proportion. This research used a single subject research method with the study subjects of the 7th-grade slow learners at one private junior high school. The research data were collected in audio and video recordings, photographs, and student worksheets. Data were analyzed by using in and between conditions with the A-B research design. The results showed that the IRME approach improves the mathematical understanding of slow learners in direct and inverse proportion concepts. Lastly, this research can contribute as alternative solutions to answer the gap in effective learning for slow learner students.